Peran Perempuan dalam Video Musik Bertaut Karya Nadin Amizah dan Implementasinya dalam Pendidikan Karakter - Fatimatuz Zahroh; Masyithah Maghfirah Rizam; Kristanti Ayuanita (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
The music video with title Bertaut by Nadin Amizah depicts the life of a family consisting of only women. The absence of men in a family shows a new order that is separated from the habits, structures, and social systems of society that regard men as the control gender in the family. Women are able to act as single parents, act as mothers and fathers because they have strong, independent, and responsible characters. The results of this study indicate the role of women at home and outside the home as breadwinners. Women who have loyalty always accompanies family members in happy and sad times. Women are strong figures and able to strengthen other family members who are in trouble. The results of the study can be used as guidelines for teachers in shaping the character of students who are strong, independent, responsible, and have empathy for others. Through literary learning, students can experience catharsis, reflect on the figure that is well described in the lyrics of the song so that they can adapt the good character to be themselves.